The murder of major José Rodríguez-Medel: new data - Izu Belloso, Miguel José (Huarte de San Juan. Geografía e Historia, 2023)
José Rodríguez-Medel Briones, major of the Spanish Guardia Civil, died in Pamplona on 18 July 1936 due to his refusal to join the military uprising against the Republic. There have been different theories over the years about the circumstances of his death, although none of them were academically satisfying: some only focused on justifying the crime, and some others incomplete because of the longlost documents of the judicial investigation. The chance finding after several decades of those dossiers (especially the report on the autopsy) allows the investigators to reformulate the facts and to discard some hypotheses (such as the possibility of an accident or a shooting started by either Rodríguez-Medel himself or one of his subordinates). They eventually concluded that it was a murder planned by the military who had supported the coup d’etat.